2016
DOI: 10.1242/jcs.171124
|View full text |Cite
|
Sign up to set email alerts
|

Keratin impact on PKCδ- and ASMase-mediated regulation of hepatocyte lipid raft size – implication for FasR-associated apoptosis

Abstract: Keratins are epithelial cell intermediate filament (IF) proteins that are expressed as pairs in a cell-differentiation-regulated manner. Hepatocytes express the keratin 8 and 18 pair (denoted K8/K18) of IFs, and a loss of K8 or K18, as in K8-null mice, leads to degradation of the keratin partner. We have previously reported that a K8/K18 loss in hepatocytes leads to altered cell surface lipid raft distribution and more efficient Fas receptor (FasR, also known as TNFRSF6)-mediated apoptosis. We demonstrate her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…This partition uncovers the essential role that lipid rafts play in enabling efficient PI3K/Akt signaling (47). Moreover, we have shown recently that loss of K8/K18 IFs in hepatocytes affects lipid raft size and organization (33, 36). On this basis, we compared the impact of lipid raft integrity on IR‐stimulated signaling in WT vs .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This partition uncovers the essential role that lipid rafts play in enabling efficient PI3K/Akt signaling (47). Moreover, we have shown recently that loss of K8/K18 IFs in hepatocytes affects lipid raft size and organization (33, 36). On this basis, we compared the impact of lipid raft integrity on IR‐stimulated signaling in WT vs .…”
Section: Resultsmentioning
confidence: 99%
“…Lipid rafts are structurally defined as dynamic membrane microdomains that are enriched in cholesterol, sphingolipids, and PIPs (57). Dynamically, small rafts coalesce into domains of various sizes via the accumulation of ceramide derived from the hydrolysis of sphingomyelin, the substrate of the acid sphingomyelinase (ASMase) (36). Functionally, accumulating evidence reveals that lipid rafts play important roles in signal transduction by providing platforms at the surface membrane (57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid rafts play a role in regulation of UVB‐induced apoptosis of skin cells . By changing major components upon stimuli, lipid rafts regulate apoptotic signaling pathways by recruiting as well as inducing aggregation, and activation of lipid raft‐associated proteins, including but not limited to membrane receptors (such as Fas, CD5, and CD20), kinases (such as Akt, JNK, Src, and PKC), and calcium channels . Our recent report indicated that PHB translocates onto lipid rafts upon UVB irradiation .…”
Section: Introductionmentioning
confidence: 99%